Efficacy of a training programme to support the application of the guideline evidence-based health information: study protocol of a randomised controlled trial - Lühnen, Julia (Trials, 2020)
BACKGROUND: The evidence-based guideline entitled guideline evidence-based health information emerged from the German Network for Evidence-based Medicine (DNEbM) and was published in February 2017. The guideline addresses providers of health information and its goal is to improve the quality of health information. In addition, we explored the competences of providers of health information and developed a training programme. The aim of this study is to evaluate the efficacy of a training programme addressing providers of health information to support the application of the guideline evidence-based health information. We expected the intervention to improve the quality of health information in comparison to the provision of the guideline on its own. METHODS/DESIGN: The trial uses a superiority randomised control group design with 10 months’ follow-up. Twenty-six providers of health information (groups with up to ten members) will be enrolled to compare the intervention (guideline and training programme) with usual care (a publicly available guideline). The 5-day training programme comprises an evidence-based medicine training module and a module to prepare the application of the guideline. The primary outcome parameter is the quality of the health information. Quality is operationalised as the extent of adherence to the guideline’s recommendations. Each provider will prepare a single health information item informing a health-related decision on a topic freely chosen before randomisation. The quality of this information will be rated using the Mapping Health Information Quality (MAPPinfo) Checklist. An accompanying process evaluation will then be conducted. DISCUSSION: The study results should show whether the efficacy of the intervention justifies implementation of the training programme to enhance health information developers’ competences in evidence-based medicine and to ensure high-quality evidence-based health information (EBHI) in the long term. TRIAL REGISTRATION: ISRCTN registry, ID: ISRCTN96941060. Registered on 7 March 2019.